Study of Gene Expression Variation of Heat Shock Factor 1 and Estimates of the Concentration of Epithelial- Derived Neutrophil- Activating Protein-78, and Ability for Bacterial Biofilm Formation in Patients with Tonsillitis - Namareq Ataallah Mohemeed; Suha Maher Abed (Diyala Journal of Medicine, 2025)
Background: Tonsillitis is an inflammation of the tonsils, often spreading to the adenoids and lingual tonsils. It is influenced by immune and genetic factors. This study aimed to evaluate the gene expression of Heat Shock Factor 1(HSF1), a protein that regulates cellular responses to stress, especially heat stress, and to measure the concentration of epithelial-derived neutrophil- activating protein-78, a chemokine involved in neutrophil activation and recruitment during inflammation. The study also sought to explore the relationship between these molecules and their roles in inflammation and stress responses. Additionally, it aimed to isolate bacterial species responsible for tonsillitis and assess their ability to form biofilms.